PENGARUH PENJUALAN ADAPTIF, KEMAMPUAN MENDENGAR DAN ORIENTASI PELANGGAN TERHADAP KINERJA TENAGA PENJUAL JASA HOTEL BINTANG 4 & 5 DI YOGYAKARTA - Leonita Agustina (Jurnal Manajemen, 2016)
The purpose of this exploratory was to examine the possible impact of the content adaptive selling, listening and customer orientation, based sales performance. Eighty eight sales people were surveyed by questionnaire. Result indicated that adaptive selling positively influence sales performance. Listening positively influence sales performance. Customer orientation positively influence sales performance. Listening is a stronger influence on sales performance. All result was using a hipotesis test. Keywords : adaptive selling, listening, customer orientation.